Improvement of eosinophilic chronic rhinosinusitis after infection with severe acute respiratory syndrome corona virus 2 during dupilumab therapy: A case report - Koike-Ieki, Mariko; Kagoya, Ryoji; Toma-Hirano, Makiko; Sasajima, Yuko; Ito, Ken (Frontiers in Allergy, 2023)
Eosinophilic chronic rhinosinusitis (ECRS) is an intractable type 2 inflammatory disease of the paranasal sinuses that persists even after endoscopic sinus surgery (ESS) and systemic corticosteroid therapy. Dupilumab, a monoclonal antibody against the shared receptor components of interleukin (IL)-4 and IL-13, is a novel and effective treatment option for ECRS. Herein, an atypical case of ECRS that improved after infection with severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) during dupilumab therapy is reported. A 40-year-old man with a history of ESS for ECRS visited our hospital with complaints of nasal congestion and dysosmia. Nasal endoscopy revealed bilateral nasal polyps occupying the nasal cavity. Computed tomography (CT) revealed a soft tissue density lesion filling all sinuses on both sides. Based on these findings, ECRS recurrence was confirmed; however, 3 years of subsequent corticosteroid therapy did not improve disease activity. Accordingly, dupilumab therapy was initiated, although 6 months of therapy resulted in only slight improvement in ECRS. Eight months after the initiation of dupilumab therapy, the patient was infected with SARS-CoV-2; thereafter, he noticed an improvement in smell. Nasal endoscopy and sinus CT revealed a marked reduction in nasal polyps and soft tissue density lesions of the sinuses, respectively. With continued dupilumab therapy, no re-exacerbation of ECRS was confirmed at the 6-month follow-up from SARS-CoV-2 infection. Currently, there are no reports describing the impact of SARS-CoV-2 infection on ECRS. As such, careful follow-up and accumulation of cases are necessary.